2021
DOI: 10.1126/science.abd4453
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of an intact clock reveals mechanisms of circadian timekeeping

Abstract: A biological clock in a test tube The biological clock of cyanobacteria, which remarkably requires just three proteins, has been reconstituted in vitro in a system that allows detailed study of its inputs and outputs, bringing new understanding of how environmental signals can influence a biological oscillator and how the clock controls cellular events such as gene transcription. Chavan et al . extended the known in vitro function of the core clock components to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 80 publications
1
73
0
Order By: Relevance
“…In turn, these oscillations -acting through the transcription factor RpaA -lead to an almost global circadian control of gene expression (Liu et al, 1995;Markson et al, 2013). Cyanobacteria have been crucial to our understanding of the inner and outer workings of the circadian clock; due in part to the post-translational nature of their oscillator (Tomita et al, 2005;Rust et al, 2007) and the fact that the interactions of clock proteins amongst themselves and with DNA can be studied in vitro (Nakajima et al, 2005;Chavan et al, 2021), we have now atomic-level resolution of clock proteins and their interactions (Pattanayek et al, 2004;Ye et al, 2004;Iwase et al, 2005;Johnson et al, 2008;Abe et al, 2015;Tseng et al, 2017;Hong et al, 2018;Mori et al, 2018), and due to cyanobacteria's fast life cycle and ease of growth, we can use them to demonstrate that having a circadian clock is advantageous by direct assessments of fitness (Ouyang et al, 1998;Woelfle et al, 2004;Ma et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, these oscillations -acting through the transcription factor RpaA -lead to an almost global circadian control of gene expression (Liu et al, 1995;Markson et al, 2013). Cyanobacteria have been crucial to our understanding of the inner and outer workings of the circadian clock; due in part to the post-translational nature of their oscillator (Tomita et al, 2005;Rust et al, 2007) and the fact that the interactions of clock proteins amongst themselves and with DNA can be studied in vitro (Nakajima et al, 2005;Chavan et al, 2021), we have now atomic-level resolution of clock proteins and their interactions (Pattanayek et al, 2004;Ye et al, 2004;Iwase et al, 2005;Johnson et al, 2008;Abe et al, 2015;Tseng et al, 2017;Hong et al, 2018;Mori et al, 2018), and due to cyanobacteria's fast life cycle and ease of growth, we can use them to demonstrate that having a circadian clock is advantageous by direct assessments of fitness (Ouyang et al, 1998;Woelfle et al, 2004;Ma et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The phenotypic relationship between the RpaA-Q121 arrhythmic and RpaA-L4 suppressor mutations was confirmed by reconstructing rpaA mutation combinations via CRISPR-Cas12a engineering ( 66 ). In addition to its role as the transcriptional response regulator of the circadian clock, RpaA plays a critical role in redox management, and rpaA -null mutants become inviable in darkness ( 67 ).…”
Section: Resultsmentioning
confidence: 98%
“…These results suggested that the crm1 mutation had no cis -regulatory impact on rpaA and, instead, perturbed clock-controlled gene expression through an unknown mechanism ( 65 ). However, we recently discovered that the phenotypes ascribed to crm derive from an unusual allele of rpaA ( 66 ).…”
Section: Resultsmentioning
confidence: 99%
“…We expect that the synchronysation properties of the clock will also be enhanced by TTR regulation. In the future, we should to include the key proteins RpaA and SasA in the models, to be able to describe quantitatively how the clock's time is read as an output [11][12][13].…”
Section: Discussionmentioning
confidence: 99%